Exploring Prescription Patterns and Patient Characteristics in Antiepileptic Therapy: A Retrospective Observational Study: Menjelajahi Pola Resep dan Karakteristik Pasien dalam Terapi Antiepilepsi: Studi Observasional Retrospektif - Martanty Aditya; Godeliva Adriani Hendra; Putera Maitreya (Academia Open, 2023)
This retrospective observational study aimed to provide an overview of prescribed antiepileptic therapy utilization and patient profiles. Conducted at a Neurology Polyclinic, data from December 2022 to January 2023 were analyzed descriptively. Among 35 eligible patients, the majority were male (68.57%), aged 15-25 years (48.57%), with long-standing epilepsy (54.28%), and absence of recent seizures (54.28%) and comorbidities (62.85%). Monotherapy was employed for 51.43%, while 48.57% received combination therapy. Phenytoin emerged as the most frequently prescribed monotherapy (25.71%), and valproic acid combined with phenytoin was the prominent combination (14.28%). This study highlights the prevalence of phenytoin and valproic acid usage, suggesting the need for further investigation into their efficacy and implications for epilepsy management. Highlights: Diverse Prescription Patterns: The study reveals a range of antiepileptic therapy prescriptions, with phenytoin and valproic acid being the predominant choices in both single and combination forms. Patient Profiles and Demographics: The analysis focuses on male-dominated respondents aged 15-25 years, emphasizing the importance of understanding patient characteristics for tailored epilepsy management strategies. Implications for Treatment Strategies: The findings underscore the significance of evaluating the efficacy and clinical implications of commonly prescribed antiepileptic drugs, guiding clinicians in optimizing epilepsy treatment regimens. Keywords: Antiepileptic therapy, Prescription patterns, Patient characteristics, Epilepsy management, Combination therapy.